2016
DOI: 10.1186/s12903-016-0239-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of light-curing distance on degree of conversion and cytotoxicity of etch-and-rinse and self-etch adhesives

Abstract: BackgroundThe degree of conversion (DC) of resin based materials depends, beside other factors, on the light-intensity applied during light curing. A lower DC might be correlated with an increased cytotoxicity of the respective materials.Therefore, aim of the present study was to investigate the influence of the distance between light-curing tip and adhesives on their cytotoxicity and degree of conversion (DC).MethodsFor the cytotoxicity assay, a total of 98 bovine dentine samples were prepared, distributed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 50 publications
(61 reference statements)
2
23
0
Order By: Relevance
“…One important finding of our screening study is that Self-Etch and Etch-and-Rinse adhesives showed no statistically significant difference in the observed cytotoxic effects in terms of the qualitative evaluation and the reactivity index. This is in accordance with other studies [14][15][16][17][18][19]. Self-etch dentin adhesives showed more cytotoxicity regarding the quantitative evaluation, which is also in line with previous studies [14,24,[26][27][28].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…One important finding of our screening study is that Self-Etch and Etch-and-Rinse adhesives showed no statistically significant difference in the observed cytotoxic effects in terms of the qualitative evaluation and the reactivity index. This is in accordance with other studies [14][15][16][17][18][19]. Self-etch dentin adhesives showed more cytotoxicity regarding the quantitative evaluation, which is also in line with previous studies [14,24,[26][27][28].…”
Section: Discussionsupporting
confidence: 93%
“…Contradictory, other studies found that Etch-and-Rinse adhesives were more cytotoxic [11,17,[20][21][22][23][24][25]. However, in all of the comparative studies, other methods, materials and their combinations were used [11,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. It should be noted that in the clinical application of Etch-and-Rinse adhesives conditioning with 37% phosphoric acid is necessary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are many researchers studying the cytotoxicity of different generations of dental adhesives 8,16,[62][63][64][65] , studies on the cytotoxicity of universal adhesives are even limited 66,67) . In addition to that, despite the above-mentioned studies, to the authors knowledge, there are no studies that have evaluated the cytotoxicity of universal adhesives using real-time and continuous analysis of cell vitality.…”
Section: Discussionmentioning
confidence: 99%
“…Degree of conversion was measured using an Attenuated Total Reflectance/ Fourier Transform Infra-Red spectrometer (ATR/ FTIR) (Vertex 70, Bruker Company, Germany) 4,10 . All the data were recorded and plotted on a special computer software (OPUS Bruker Spectroscopy Software, version 7, Germany) to draw the linear graphs from which the degree of conversion of each specimen was calculated.…”
Section: Becton and Dickenson (Bd) Companymentioning
confidence: 99%